2006
DOI: 10.1177/1471301206067115
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and behaviour in dementia

Abstract: Physical activity can have a positive impact on cognition and well-being in older people. This article reviews and evaluates the effects of planned physical activity programmes on mood, sleep and functional ability in people with dementia. A total of 27 studies between 1974 and 2005 were found. Of these, four included participants living at home, two involved participants who were living either at home or in care homes and 21 included participants living solely in care homes. Since psychosocial intervention ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…Corresponding findings are also present in other studies9,10 among people with dementia. In the study by Cedervall and Åberg,15 one next of kin found physical activity to be very positive because the activity provided benefits such as peace and quiet, and pleasure for the person with dementia.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Corresponding findings are also present in other studies9,10 among people with dementia. In the study by Cedervall and Åberg,15 one next of kin found physical activity to be very positive because the activity provided benefits such as peace and quiet, and pleasure for the person with dementia.…”
Section: Discussionsupporting
confidence: 88%
“…The fact that next of kin as caregivers have a need for information and support about dementia disease is supported in studies 46,8. Likewise, there is support for the positive impact of physical9 and social activities10 for the perception of wellbeing in home-dwelling people with dementia. There has been a great focus on dementia sufferers in Norway, and more research that can facilitate the provision of an active and social life is requested 7.…”
Section: Introductionmentioning
confidence: 95%
“…Music therapy has been found to facilitate active participation even very late in dementia [16,30]. A possible hypothesis is that the amygdala, one of the last parts of the brain to be affected by dementia, still receives, reacts to and expresses mood and emotion in PWD.…”
Section: Discussionmentioning
confidence: 99%
“…rest-activity rhythm [30]. In older persons with or without dementia, a physical activity intervention seems to be effective [24,31-34], especially in people with poor sleep at baseline [33]. These studies, however, are scarce since the majority of physical activity intervention studies are multi-dimensional, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…These studies, however, are scarce since the majority of physical activity intervention studies are multi-dimensional, i.e. physical activity is combined with bright light or a decrease in noise at night [24,30,31,33]. Such a combination hampers the understanding of which intervention is (most) effective [35].…”
Section: Introductionmentioning
confidence: 99%